Genetic trends in the Zimbabwe’s national maize breeding program over two decades - Mukaro, Ronica; Chaingeni, Davison; Sneller, Clay; Cairns, Jill E.; Musundire, Lennin; Prasanna, Boddupalli M.; Mavankeni, Busiso Olga; Das, Biswanath; Mulanya, Mable; Chivasa, Walter; Mhike, Xavier; Ndhlela, Thokozile; et al. (Frontiers in Plant Science, 2024)
Monitoring genetic gains within breeding programs is a critical component for continuous improvement. While several national breeding programs in Africa have assessed genetic gain using era studies, this study is the first to use two decades of historical data to estimate genetic trends within a national breeding program. The objective of this study was to assess genetic trends within the final two stages of Zimbabwe’s Department of Research & Specialist Services maize breeding pipeline between 2002 and 2021. Data from 107 intermediate and 162 advanced variety trials, comprising of 716 and 398 entries, respectively, was analyzed. Trials were conducted under optimal, managed drought stress, low nitrogen stress, low pH, random stress, and disease pressure (maize streak virus (MSV), grey leaf spot (GLS), and turcicum leaf blight under artificial inoculation. There were positive and significant genetic gains for grain yield across management conditions (28–35 kg ha-1 yr-1), under high-yield potential environments (17–61 kg ha-1 yr-1), and under low-yield potential environments (0–16 kg ha-1 yr-1). No significant changes were observed in plant and ear height over the study period. Stalk and root lodging, as well as susceptibility to MSV and GLS, significantly decreased over the study period. New breeding technologies need to be incorporated into the program to further increase the rate of genetic gain in the maize breeding programs and to effectively meet future needs.